How to Weigh a Donkey in the Kenyan Countryside. Issue 4 (3rd October 2014) - Milner, Kate; Rougier, Jonathan
Abstract: Donkeys play a crucial role in the lives of rural Kenyans. When they fall sick, vets need a quick and accurate method of weighing the animals to administer the right dosage of drugs. The humble nomogram can help, as Kate Milner and Jonathan Rougier explain.